Trait Emotional Intelligence Profiles of Parents With Drug Addiction and of Their Offspring - Aslanidou, Georgia S.; Petrides, K. V.; Stogiannidou, Ariadni (Frontiers in Psychology, 2018)
This study examines the relationship between trait emotional intelligence (trait EI) and general health (General Health; GHQ-28) in two samples of Greek parents with (n = 52; Mage = 39.78; SDage = 6.68; 41 men, 11 women) and without (n = 51; Mage = 43.53; SDage = 4.61; 40 men, 11 women) addiction problems. In addition, it compares the trait EI scores of their offspring (N = 81; Mage = 11.71; SDage = 2.15; 51 boys, 30 girls). Results showed that parents with drug addiction exhibited lower levels of trait EI and poorer general health than peers. In addition, global trait EI and two of its subscales, Well-being and Emotionality, had stronger correlations with depression in the addiction than in the comparison group. Well-being was a significant predictor of general health and its subscales (Somatic symptoms, Anxiety/insomnia, Social dysfunction, and Severe depression) in both groups. No differences were found between the offspring of the two groups.